What Causes Insolvency? A Study Regarding Big and Medium Romanian Enterprises Going Bankrupt in 2013 - Tudor Andrei Radulescu; Carmen Nistor (CES Working Papers, 2014)
The failure of a company, whether insolvency or bankruptcy, has been a topic featured by countless researchers from various fields over time. In an attempt to counteract this negative phenomenon most of the studies focused on developing bankruptcy prediction models, omitting the actual reasons that caused the insolvency. In the present article we will try to determine the main reasons causing insolvency among the largest companies in Romania in 2013. In this purpose, we made a Top 10 Romanian companies which became insolvent in 2013 taking into consideration the report published by Euler Hermes in 2014 “Economic Outlook. Insolvency World Cup 2014: Who will score fewer insolvencies?”. Subsequently, we examine “The Report on the causes and circumstances that led to the insolvency of the debtor" for each individual company from the proposed top. After analyzing the reports for all ten companies studied we found that an increasing of indebtedness and debt collection period, with disinvestment and poor management were the main causes that led to the insolvency in 2013 of the Romanian companies studied.
Keywords: G33; 330; insolvency; determinants of bankruptcy; Romania